Strength training intensity and volume affect performance of young kayakers/canoeists - Gäbler, M.; Berberyan, H. S.; Prieske, O.; Elferink-Gemser, M. T.; Hortobagyi, T.; Warnke, T.; Granacher, U. (Frontiers in Physiology, 2021)
Purpose: The aim of this study was to compare the effects of moderate intensity, low volume (MILV) vs. low intensity, high volume (LIHV) strength training on sport-specific performance, measures of muscular fitness, and skeletal muscle mass in young kayakers and canoeists.